2006
DOI: 10.1007/s00213-006-0562-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress modulation on morphine-induced conditioned place preferences and plasma corticosterone levels in Fischer, Lewis, and Sprague–Dawley rat strains

Abstract: These data suggest that the relationship between stress and drug use may be nonmonotonic. The use of these inbred strains in genetic analysis of drug addiction may require reexamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 51 publications
1
21
2
Order By: Relevance
“…Results from Experiment 1 suggest that acute stress enhances the rewarding effects of lower nicotine doses as expressed by a reduction in the number of conditioning trials needed to produce CPP. N-NP (controls: S-NP) conditioning with nicotine (0.6 mg/kg, s.c.) or saline in the initially non-preferred side of the CPP apparatus, S-P conditioning with saline in the initially preferred side of the CPP apparatus Such results are in line with studies showing that a single stressor exposure 24 h before conditioning enhances amphetamine (Capriles and Cancela 1999), morphine (Dai et al 2006;Grakalic et al 2006;Will et al 1998), and oxycodone (Der-Avakian et al 2007) CPP. Findings from preclinical studies indicate that acute stress plays an important role in relapse to nicotine seeking as measured by reinstatement of nicotine CPP (Leão et al 2009) and self-administration (Bruijnzeel et al 2009;Buczek et al 1999;Zislis et al 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from Experiment 1 suggest that acute stress enhances the rewarding effects of lower nicotine doses as expressed by a reduction in the number of conditioning trials needed to produce CPP. N-NP (controls: S-NP) conditioning with nicotine (0.6 mg/kg, s.c.) or saline in the initially non-preferred side of the CPP apparatus, S-P conditioning with saline in the initially preferred side of the CPP apparatus Such results are in line with studies showing that a single stressor exposure 24 h before conditioning enhances amphetamine (Capriles and Cancela 1999), morphine (Dai et al 2006;Grakalic et al 2006;Will et al 1998), and oxycodone (Der-Avakian et al 2007) CPP. Findings from preclinical studies indicate that acute stress plays an important role in relapse to nicotine seeking as measured by reinstatement of nicotine CPP (Leão et al 2009) and self-administration (Bruijnzeel et al 2009;Buczek et al 1999;Zislis et al 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Acute stress enhances the rewarding effects of several addictive drugs in rodents as measured using conditioned place preference (CPP) (Capriles and Cancela 1999;Dai et al 2006;Der-Avakian et al 2007;Grakalic et al 2006;Matsuzawa et al 1998a, b;Will et al 1998). The mechanisms by which this occurs have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…The relationship between HPA activity and drug withdrawal-induced behavior alteration and changes in the brain stress system has not been elucidated, and contradictory results have been shown. For example, morphine-induced conditioned place preference was decreased by antalarmin, whereas this antagonist did not antagonize the increase in plasma corticosterone levels (Grakalic et al, 2006), which suggests that the changes in place preference conditioning induced by CRF1R blockade are not related to changes in HPA activity. In addition, CRF1R has been shown to play a major role in mediating the effects of CRF on behavioral responses to lorazepam withdrawal but not some of the neuroendocrine effects.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, we predicted that the PNS-exposed pups would be significantly more motivated to interact with the dam, and therefore spend significantly more time in the maternally-conditioned odor portion of the COP apparatus compared to the control pups. Several lines of research have shown that increases in HPA activity lead to enhanced or stronger place preference (Dai et al 2006; Grakalic et al 2006). Yang et al (2006) demonstrated that PNS enhanced conditioned place preference to morphine (Yang et al 2006).…”
Section: Introductionmentioning
confidence: 99%